The River of Heaven : The Haiku of Bashō, Buson, Issa, and Shiki - Compiled By Aitken, Robert, 1917-2010 (Berkeley Counterpoint, 2011)
Known to many as the study of quiet stillness and introspection, Zen Buddhism distinguishes itself through brilliant flashes of insight and its terseness of expression. In River of Heaven these concepts and pillars lend themselves to an exploration of Haiku, one of the most delicate and interpretive poetic forms in the world. The haiku verse form, with its rigid structure and organic description is a superb means of studying Zen modes of thought because its seventeen syllables impose a limitation that confines the poet to vital experience. In Haiku as in Buddhism, the silences are as expressiv.
Keywords: Kobayashi, Issa, 1763-1827